Inframe insertion and splice site variants in MFGE8 associate with protection against coronary atherosclerosis - Ruotsalainen Sanni E.; Surakka Ida; Mars Nina; Karjalainen Juha; Kurki Mitja; Kanai Masahiro; Krebs Kristi; Graham Sarah; Mishra Pashupati P.; Mishra Binisha H.; Sinisalo Juha; Palta Priit; et al. (NATURE PORTFOLIO, 2022)
A genome-wide association study identifies MFGE8 as protective against coronary atherosclerosis in European and East Asian populations.Cardiovascular diseases are the leading cause of premature death and disability worldwide, with both genetic and environmental determinants. While genome-wide association studies have identified multiple genetic loci associated with cardiovascular diseases, exact genes driving these associations remain mostly uncovered. Due to Finland's population history, many deleterious and high-impact variants are enriched in the Finnish population giving a possibility to find genetic associations for protein-truncating variants that likely tie the association to a gene and that would not be detected elsewhere. In a large Finnish biobank study FinnGen, we identified an association between an inframe insertion rs534125149 in MFGE8 (encoding lactadherin) and protection against coronary atherosclerosis. This variant is highly enriched in Finland, and the protective association was replicated in meta-analysis of BioBank Japan and Estonian biobank. Additionally, we identified a protective association between splice acceptor variant rs201988637 in MFGE8 and coronary atherosclerosis, independent of the rs534125149, with no significant risk-increasing associations. This variant was also associated with lower pulse pressure, pointing towards a function of MFGE8 in arterial aging also in humans in addition to previous evidence in mice. In conclusion, our results suggest that inhibiting the production of lactadherin could lower the risk for coronary heart disease substantially.